1994
DOI: 10.1159/000119160
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG Changes in Cocaine Withdrawal: Evidence for Long-Term CNS Effects

Abstract: Quantitative EEG changes were studied during cocaine withdrawal in 36 subjects. All subjects had used cocaine orally (n = 28) or intravenously (n = 8) within 48 h of admission to an inpatient unit. EEGs were recorded 2 and 6 days following admission. Nine subjects returned for a 1-month follow-up EEG. Modal EEG frequency significantly decreased on day 6 compared to day 2. The most dramatic change in both absolute and relative power from day 2 to day 6 was a decrease in the beta2 (18–26 Hz) band. Those subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 3 publications
2
26
2
Order By: Relevance
“…Our group, and others, have reported excess alpha activity (Alper et al, 1990;Lukas, 1991;Herning et al, 1994;Roemer et al, 1995;Prichep et al, 1996a) and decreased delta activity (Alper et al, 1990;Noldy et al, 1994;Roemer et al, 1995;Prichep et al, 1996a, b), while others have reported increased beta power (Herning et al, 1985(Herning et al, , 1997Noldy et al, 1994) in cocaine-dependent patients, recorded in eyes closed, resting conditions. The qEEG abnormalities, primarily found in anterior cortical regions, were shown to correlate with the amount of prior cocaine use (Prichep et al, 1996a;Herning et al, 1997;Roemer et al, 1995).…”
Section: Introductionmentioning
confidence: 47%
“…Our group, and others, have reported excess alpha activity (Alper et al, 1990;Lukas, 1991;Herning et al, 1994;Roemer et al, 1995;Prichep et al, 1996a) and decreased delta activity (Alper et al, 1990;Noldy et al, 1994;Roemer et al, 1995;Prichep et al, 1996a, b), while others have reported increased beta power (Herning et al, 1985(Herning et al, , 1997Noldy et al, 1994) in cocaine-dependent patients, recorded in eyes closed, resting conditions. The qEEG abnormalities, primarily found in anterior cortical regions, were shown to correlate with the amount of prior cocaine use (Prichep et al, 1996a;Herning et al, 1997;Roemer et al, 1995).…”
Section: Introductionmentioning
confidence: 47%
“…This was replicated in subsequent studies with a larger number of participants (Alper, 1999;Alper, Chabot, Kim, Prichep, & John, 1990;Alper, Prichep, Kowalik, Rosenthal, & John, 1998;Costa & Bauer, 1997;Herning et al, 1985;Noldy, Santos, Politzer, Blair, & Carlen, 1994;Prichep, Alper, Kowalik, & Rosenthal, 1996;Prichep et al, 1999;Prichep et al, 2002;Roemer et al, 1995). Beside beta effects, studies have reported an increase in delta activity (Herning et al, 1985) and frontal alpha activity (Herning, Glover, Koeppl, et al, 1994), whereas others have reported an increase in alpha wave EEG associated with bursts of cocaine-induced euphoria (Lukas, 1991).…”
Section: Qeeg In Sudmentioning
confidence: 85%
“…A number of specific qEEG abnormalities have been described as specific to suspected neurotoxicities associated with chronic stimulant abuse. These studies (Alper et al, 1990;Noldy et al, 1994;Prichep et al, 1996;Roemer et al, 1995;Trudeau, Thuras, & Stockley, 1999) based on reasonably uniform abstinence times and employing different EEG technology and analytical approaches, have produced remarkably similar findings of alpha relative amplitude excess with delta relative amplitude deficit that is striking. Excess alpha amplitude with slowing of alpha frequency associated with chronic cannabis abuse has been reported (Struve et al, 1998).…”
Section: Clinical Considerations: Comorbidities Of Sud and Implicatiomentioning
confidence: 87%
See 2 more Smart Citations